'Saving' the child in Victorian Dundee - Chrissie Urquhart (Scottish Journal of Residential Child Care)
Similar to current disquiet, public anxiety and political debate fuelled concerns amongst the Victorians about juvenile 'delinquency' and child neglect. Contemporary observers argued that it was the drunkenness, ignorance, promiscuity, and irresponsibility of parents which were responsible for the 'gangs' of disorderly and offending children 'swarming' the streets of Victorian towns (Pearson, 1983; Platt, 1969; Shore, 1999). The children of the 'culpable' poor were believed to be at particular risk of drifting into criminality, as not only were they influenced by their unreliable and unworthy parents but they had also inherited all the susceptibilities and propensities of their forebears. What to do with these children became a prominent preoccupation of the era. A group of reformers, many of whom were evangelicals, argued that the salvation of these children could only be achieved through religious- based moral training. (These reformers are characterised by the term 'child savers'). They had a resolute belief in the righteousness of their cause: not only to protect the child from the risk of criminality but also to protect society from the perceived growth in lawlessness. The rhetoric of the 'child savers' was the protection from depravity and corruption of a large group of vulnerable children, but the methods established within the institutions they founded, and the subsequent legislation, sought to correct the behaviour of the culpable poor through the retraining and reforming of their children.